The primary English teacher's guide - Brewster, Jean.; Ellis, Gali.; Girard, Denis (England : Pearson Education Limited, 2002)
The new edition of this definitive guide for primary teachers, teacher trainers and trainees covers the most recent developments in language learning theories and approaches. It offers you lots of practical suggestions on selecting materials, lesson planning, managing the classroom and using resources effectively.
Includes bibliographical references.
Keywords: English language -- Study and teaching (Elementary) -- Great Britain; English language -- Study and teaching (Elementary).